2012
DOI: 10.1051/0004-6361/201118095
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetry of the binary PDS 144

Abstract: Aims. Our goal is to study the circumstellar environment associated with each component of the wide intermediate-mass pre-main sequence binary system PDS 144 using broadband polarimetry. Methods. We present near-infrared (NIR) linear polarimetric observations of PDS 144 gathered with the IAGPOL imaging polarimeter along with the CamIV infrared camera at the Observatório do Pico dos Dias (OPD). In addition, we re-analyzed OPD archive optical polarization to separate the binary and estimate the interstellar pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…type: A5V), lacks PAH emission. PDS 144N & S are found to have intrinsic polarization, which is aligned with the local magnetic field and the jet axis (Pereyra et al 2012), and the high NIR polarization of the PDS 144N disk is in favor of the presence of small grains similar to those of the diffuse ISM. Schütz et al (2009) found that the spectral profile of the 8.6 µm PAH feature is similar to that of PAHs in the ISM (i.e., PAH class A as determined by Peeters et al 2002), whereas the peak wavelength of the 11.2 µm PAH feature is red-shifted compared to those of class A and B profiles.…”
Section: A53 Mwc 1080mentioning
confidence: 86%
“…type: A5V), lacks PAH emission. PDS 144N & S are found to have intrinsic polarization, which is aligned with the local magnetic field and the jet axis (Pereyra et al 2012), and the high NIR polarization of the PDS 144N disk is in favor of the presence of small grains similar to those of the diffuse ISM. Schütz et al (2009) found that the spectral profile of the 8.6 µm PAH feature is similar to that of PAHs in the ISM (i.e., PAH class A as determined by Peeters et al 2002), whereas the peak wavelength of the 11.2 µm PAH feature is red-shifted compared to those of class A and B profiles.…”
Section: A53 Mwc 1080mentioning
confidence: 86%